MERAIH SUKSES MELALUI PERSONAL BRANDING BAGI GEN Z DI SMK LABORATORIUM GLOBAL CIKARANG - Damiyana, Damdam; Darlin, Evalina; Hanarti, Inna (JURNAL ABDIMAS PLJ, 2023)
As a prospective employee, you must understand what soft skills the job seeker requires before starting work. During recruitment, one of the effective searches for human resources is administrative selection through Curriculum Vitae (CV), then interviews, and having personal branding. Through this process, organizations can find out the qualities and abilities of prospective employees before undergoing the next selection test. Cikarang Global Laboratory Vocational School which has the hope of being able to continue to improve and innovate, to be able to produce quality output or graduates who are able to answer future challenges, either for work (B) or continuing their studies at higher education (M) or entrepreneurship to become successful entrepreneurs ( W) or what is usually called BMW. Therefore, students of SMK Laboratoroum Global Cikarang need to be given practical training when facing the world of work, by providing practice on how to make a good and attractive Curiculum Vitae (CV), have strong interview skills, and have unique personal branding. In line with the obligations of lecturers in the Tri Dharma of higher education, LP3I Jakarta Polytechnic lecturers have the opportunity to carry out this community service Keywords: Personal Branding, Curriculum Vitae, Interview